2016
DOI: 10.1038/srep34094
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cell Invasion into a Three Dimensional Tumor-Stroma Microenvironment

Abstract: In this study, to model 3D chemotactic tumor-stroma invasion in vitro, we developed an innovative microfluidic chip allowing side-by-side positioning of 3D hydrogel-based matrices. We were able to (1) create a dual matrix architecture that extended in a continuous manner, thus allowing invasion from one 3D matrix to another, and (2) establish distinct regions of tumor and stroma cell/ECM compositions, with a clearly demarcated tumor invasion front, thus allowing us to quantitatively analyze progression of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 72 publications
3
106
0
Order By: Relevance
“…F-actin cytoskeleton staining was quantified using Particle Analyzer Plugin ImageJ software, as described earlier. 14 The epithelial cell shape with large cell volume and roundness of the cell was calculated as described earlier. 15,16…”
Section: Secreted Vegf Level Estimationmentioning
confidence: 99%
“…F-actin cytoskeleton staining was quantified using Particle Analyzer Plugin ImageJ software, as described earlier. 14 The epithelial cell shape with large cell volume and roundness of the cell was calculated as described earlier. 15,16…”
Section: Secreted Vegf Level Estimationmentioning
confidence: 99%
“…EGF and its receptors are commonly overexpressed in many solid tumors where it is associated with increased proliferation and tumor metastasis 36. Using a hydrogel in a microfluidic system, Truong et al demonstrated significantly increased breast cancer cell migration speed and persistence in response to a transient EGF gradient 37. In order to study the effects of spatially defined EGF gradients on breast cancer invasion, Fisher et al used two‐photon confocal microscopy to photopattern discrete EGF gradients within an HA‐based hydrogel and found increased invasion of MDA‐MB‐231 cells in the presence of EGF gradients ( Figure ) 38.…”
Section: Invasion Is Directed By the Physicochemical Environmentmentioning
confidence: 99%
“…The association of CAFs in tumor microenvironments with metastasis is well established; however, the dynamics of cell–cell communication leading to cell invasion is difficult to study in vivo. Using engineered hydrogel systems, researchers have been able to elucidate mechanisms of crosstalk between CAFs and cancer cells 37,51–55…”
Section: Coculture Effects On Cell Movement Through Hydrogelsmentioning
confidence: 99%
“…Experimental set ups span a range of complexities from simple hydrogel plugs in a multi-well plate (37) and filter insert (38), to more sophisticated 3 microfluidic platforms where different cell populations can be patterned into specific structures and tissue compartments. These microfluidic approaches have enabled real time monitoring of tumour cell invasion into neighbouring stromal tissue (39)(40)(41) and revealed dynamic events such as the transition to an invasive phenotype, colonization of adjacent compartments, and tumour cell extravasation. These changes in cell migration, morphology, and proliferation would be particularly challenging to quantify in animal or other in vitro culture models.…”
Section: Introductionmentioning
confidence: 99%